International Environmental Law Violations Conflict Analysis: Israel v. Gaza in 2024 - Gunawan Yordan; Ghiffara Mustafad; Akbar M. Fabian (E3S Web of Conferences)
This study explores the environmental consequences of the Israel-Palestine conflict, emphasizing the critical role of International Environmental Law (IEL) in addressing and mitigating these impacts. Armed conflict severely disrupts ecosystems, damages infrastructure, and endangers public health, as evidenced by the extensive environmental degradation in Gaza, including contaminated water sources and destroyed essential infrastructure. Employing a doctrinal legal study methodology based on secondary data, this research examines how IEL can alleviate environmental harm caused by armed conflicts and investigates the roles of international organizations in environmental protection during such crises. The analysis focuses on the contributions of the United Nations (UN) and the United Nations Environment Programme (UNEP) in safeguarding environmental conservation and human rights amid violent conflicts. The study uniquely identifies the limitations of existing frameworks, such as the lack of ratification of international agreements by key nations and inadequate enforcement mechanisms, as primary barriers to effective environmental protection. It concludes by underscoring the urgent need for enhanced legal frameworks, stronger global collaboration, and actionable policies to prevent further environmental degradation, ensure accountability, and promote sustainable peace in conflict zones. Policymakers, scholars, and international organizations are called upon to prioritize these efforts to align environmental protection with the broader goals of human security and conflict resolution.